Peripheral T-Cell Lymphomas: A Review of Current Approaches and Hopes for the Future - Skarbnik, Alan P.; Burki, Meher; Pro, Barbara (Frontiers in Oncology, 2013)
Peripheral T-cell lymphomas (PTCL) are a diverse group of lymphoproliferative disorders, which share a common denominator of overall poor prognosis, with few exceptions. In this article, the authors review current standard of care approaches for the treatment of PTCLs, the role of stem-cell/bone marrow transplantation, and current developments in novel targeted therapies.